A composite material for a multi-stage resonant activation energy-saving device and a preparation method thereof

CN122916718APending Publication Date: 2026-10-16CHONGQING LANGFU ENVIRONMENTAL PROTECTION TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611253239.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-17
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0008]本发明的目的是提供一种多级谐振活化节能装置用复合材料及其制备方法,以解决天然气常规燃烧条件下难以充分反应,导致燃气利用率偏低,不完全燃烧还会产生一氧化碳等有害尾气的问题

Benefits of technology

1、本发明将多元无铅压电体系与钕镧稀土红外共振活化相结合,构建压电交变电场扰动与分子红外共振耦合活化机制,双重作用弱化甲烷分子C-H键,显著提升天然气预活化效果,促进充分燃烧,降低尾气CO排放,节约燃气消耗。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122916718A_ABST
    Figure CN122916718A_ABST
Patent Text Reader

Abstract

The present application relates to natural gas pretreatment material technical field, particularly to a kind of composite material for multistage resonance activation energy-saving device and its preparation method.The rare earth piezoelectric activated composite material includes: piezoelectric ceramic powder 65~85 parts, rare earth functional material powder 8~25 parts, interface regulation adjuvant 2~7 parts, inorganic bonding porous carrier powder 5~15 parts.The present application is through mid-infrared characteristic spectrum resonance absorption, microseismic wave synergistic effect and molecular outer electron cloud regulation multiple mechanism, so that natural gas molecule inner energy increases activity promotion, and oxygen is combined more closely, can the apparent activation energy of methane is reduced to 80~100kJ / mol from 240kJ / mol, promote sufficient combustion, realize synergistic emission reduction, CO emission amount relative reduction 25%‑75%, HC emission amount relative reduction 14%‑75%.The present application integrated ceramic structure is stable, need not external power supply, adaptation various gas combustion equipment, process is simple, suitable for large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of natural gas pretreatment materials technology, and in particular to a composite material for a multi-stage resonant activation energy-saving device and its preparation method. Background Technology

[0002] Natural gas, as a clean energy source, is widely used in household stoves, industrial furnaces, and other equipment. The main component of natural gas is methane. Methane molecules have a stable structure and high CH bond energies, making it difficult to react completely under conventional combustion conditions. This not only results in low gas utilization but also produces harmful exhaust gases such as carbon monoxide. To improve combustion efficiency, existing technologies propose using pre-activation methods to pre-treat natural gas in pipelines, weakening the chemical bonds in methane molecules and promoting complete combustion.

[0003] Current natural gas pre-activation technologies are mainly divided into two categories. The first category is the infrared radiation activation scheme, which uses far-infrared ceramic materials to radiate infrared light waves to excite the vibration of methane molecules. This scheme relies solely on photothermal effects, resulting in limited molecular activation. To achieve better results, an external heat source is often needed to heat the infrared ceramic, increasing energy consumption. At the same time, conventional infrared materials cannot accurately match the 3-5μm characteristic absorption band of methane, resulting in low resonance activation efficiency.

[0004] The second category is piezoelectric activation combustion-aiding schemes, which use single-phase piezoelectric ceramics and utilize fluid impact to generate a piezoelectric electric field that disturbs gas molecules. Most existing piezoelectric activation systems use pure barium titanate or pure potassium sodium niobate single-phase piezoelectric materials, which have limited electromechanical coupling coefficients and poor temperature adaptability; the single piezoelectric mechanism lacks auxiliary activation pathways, and the improvement in combustion efficiency is insufficient when used alone.

[0005] A few schemes have attempted to use a simple physical mixture of piezoelectric powder and infrared powder. However, this type of composite system has obvious drawbacks. First, it is just a simple mixing of powders without controlling the interface between the two phases. The charge carriers generated by the piezoelectric effect are very easy to recombine at the interface, and the mechanical energy is difficult to be effectively transferred to the infrared functional component, thus failing to form a synergistic activation effect. Second, the piezoelectric matrix mostly uses single-phase components, and the piezoelectric response intensity is insufficient under airflow excitation. Third, there is a lack of rare earth infrared functional formulations that can accurately induce methane molecule resonance. The two functions are simply superimposed, making it difficult to produce the coupling gain effect of piezoelectric electric field perturbation and infrared resonance.

[0006] In addition, some activation devices require auxiliary equipment such as external power supply and external ultrasonic excitation, which are complex in structure, difficult to install and modify, and difficult to directly adapt to existing gas transmission pipelines.

[0007] Therefore, in order to address the above problems, developing an integrated natural gas molecule pretreatment activation composite material that requires no external energy source, is driven passively by airflow, and possesses both piezoelectric field disturbance and rare earth infrared resonance activation effects, as well as high interface energy transfer efficiency, is an urgent problem to be solved in this field. Summary of the Invention

[0008] The purpose of this invention is to provide a composite material for a multi-level resonant activation energy-saving device and its preparation method, so as to solve the problem that natural gas is difficult to react fully under conventional combustion conditions, resulting in low gas utilization rate and the generation of harmful exhaust gases such as carbon monoxide due to incomplete combustion.

[0009] To achieve the above objectives, the present invention provides a rare earth piezoelectric activation composite material for a multi-level resonant activation energy-saving device, comprising the following components in parts by weight: 65-85 parts piezoelectric ceramic powder, 8-25 parts rare earth functional material powder, 2-7 parts interface regulation agent, and 5-15 parts inorganic binder porous carrier powder. Among them, piezoelectric ceramic powder is the piezoelectric main phase, rare earth functional material powder is the rare earth infrared resonance activated phase, interface regulation agent is the interface regulation phase, and inorganic binder porous carrier powder is the porous carrier phase.

[0010] Preferably, the piezoelectric ceramic powder includes barium titanate, potassium sodium niobate, sodium bismuth titanate, and bismuth ferrite.

[0011] Preferably, the mass ratio of barium titanate, potassium sodium niobate, sodium bismuth titanate, and bismuth ferrite is 46~56:9~12:7~10:3~7, and more preferably 49~52:10~11:8~9:4~6.

[0012] Preferably, the rare earth functional material powder includes neodymium oxide and lanthanum oxide, and the mass ratio of neodymium oxide to lanthanum oxide is 6~15:2~10, more preferably 6~10:2~5.

[0013] Preferably, the interface regulating agent includes zirconium dioxide and manganese dioxide, and the mass ratio of zirconium dioxide to manganese dioxide is 1~5:1~2, preferably 4:1.

[0014] Preferably, the inorganic binder porous carrier powder includes kaolin, alumina and silica, with kaolin being the most preferred.

[0015] This invention also provides a method for preparing rare-earth piezoelectric activated composite material for the above-mentioned multi-level resonant activation energy-saving device, comprising the following steps: S1. Ingredient mixing: Piezoelectric ceramic powder, rare earth functional material powder, interface control agent and inorganic binder porous carrier powder are ball-milled with a mixing grinding ball in anhydrous ethanol medium to obtain a mixture. The mixture is then dried at high temperature to obtain a mixed powder. S2, Pre-firing treatment: The mixed powder was calcined at high temperature in a muffle furnace to obtain pre-calcined powder; S3, Granulation and molding: A binder aqueous solution is added to the pre-fired powder, and after stirring, granulation, and aging, a ceramic green body is obtained by compression process. S4, Debinding and Sintering: The ceramic blank was sintered at high temperature in an air atmosphere in a muffle furnace, and after cooling, a rare earth piezoelectric composite activated ceramic material was obtained.

[0016] Preferably, the diameter of the grinding ball in S1 is 5 mm and 10 mm.

[0017] The mass ratio of the mixed grinding balls is 1:1.

[0018] The mass ratio of the material, the ball, and anhydrous ethanol is 1:2:1.

[0019] The ball milling speed is 300 rpm, and the time is 8~16h, preferably 12h.

[0020] The high-temperature drying temperature is 80~120℃, preferably 100℃, and the time is 12h.

[0021] Preferably, the high-temperature calcination temperature in S2 is 600~700℃, more preferably 650℃, and the time is 2h.

[0022] Preferably, the binder aqueous solution in S3 is a polyvinyl alcohol binder aqueous solution with a concentration of 5% and an addition amount of 8% of the mass of the pre-calcined powder.

[0023] The aging time is 24 hours.

[0024] The compression process is a dry compression process, with a pressure of 15~30MPa, preferably 20MPa, and a holding time of 60s.

[0025] Preferably, the high-temperature debinding sintering parameters in S4 are as follows: heating at a rate of 1.5℃ / min to 450~550℃, preferably 500℃, holding for 2~3h, preferably 2h, then heating at a rate of 2℃ / min to 1120~1220℃, preferably 1160℃, holding for 2~4h, preferably 3h.

[0026] The present invention has the following beneficial effects: 1. This invention combines a multi-element lead-free piezoelectric system with neodymium lanthanum rare earth infrared resonance activation to construct a piezoelectric alternating electric field disturbance and molecular infrared resonance coupling activation mechanism. The dual effect weakens the CH bond of methane molecules, significantly improves the pre-activation effect of natural gas, promotes complete combustion, reduces CO emissions in exhaust gas, and saves fuel consumption.

[0027] 2. A quaternary composite piezoelectric matrix of barium titanate, potassium sodium niobate, sodium bismuth titanate and bismuth ferrite is adopted to overcome the defects of low electromechanical coupling efficiency and poor temperature adaptability of single-phase piezoelectric ceramics, and to stably generate micro-vibration and local alternating electric field under continuous airflow disturbance.

[0028] 3. By precisely controlling the interface structure and oxygen vacancy concentration through the binary interface additives of zirconium dioxide and manganese dioxide, the recombination probability of charge carriers is reduced, and the piezoelectric energy is efficiently transferred to the rare earth activation center, further amplifying the synergistic activation effect.

[0029] 4. The material is an integrated sintered lead-free ceramic, which has a stable structure and is not prone to failure; it is driven by airflow mechanical energy without external power, and can be directly installed inside the gas transmission pipeline. It is easy to install and suitable for large-scale promotion and application of civil gas and industrial combustion equipment.

[0030] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. Attached Figure Description

[0031] Figure 1 A graph showing the CO concentration in natural gas at the outlet. Figure 2 A graph showing the concentrations of methane and HC in the natural gas outlet gases; Figure 3 The graph shows the activation energy of methane. Figure 4 The graph shows the relative decrease in CO and HC emissions. Detailed Implementation

[0032] The technical solution of the present invention will be further described below with reference to the accompanying drawings and embodiments. It should be noted that, unless otherwise specifically stated, the relative arrangement, numerical expressions, and values ​​of the components and steps described in these embodiments do not limit the scope of this application.

[0033] The following description of at least one exemplary embodiment is merely illustrative and is in no way intended to limit the scope of this application and its application or use.

[0034] Techniques, methods, and equipment known to those skilled in the art may not be discussed in detail, but where appropriate, they should be considered part of the specification.

[0035] In all the examples shown and discussed herein, any specific values ​​should be interpreted as merely exemplary and not as limitations. Therefore, other examples of exemplary embodiments may have different values.

[0036] Unless otherwise defined, the technical or scientific terms used in this invention shall have the ordinary meaning as understood by one of ordinary skill in the art to which this invention pertains.

[0037] The present invention employs the following working principle in its preparation: rare earth-piezoelectric composite radiation activation. The core activation material is composed of rare earth functional materials containing elements such as scandium, lanthanum, neodymium, cobalt, and thorium, combined with piezoelectric ceramics. When natural gas flows through, it generates micro-pressure fluctuations, which excite the piezoelectric material to produce micro-currents and micro-vibration waves. Simultaneously, the rare earth material, stimulated, radiates broadband electromagnetic waves outward, primarily covering the mid-infrared band (3-5 μm) where natural gas molecules have the highest absorption efficiency.

[0038] Natural gas is primarily composed of methane (CH4), whose molecular vibrational energy levels exhibit strong characteristic absorption peaks in the mid-infrared band. When flowing through an activation field, the molecules resonate and capture mid-infrared radiation energy, intensifying vibrational and rotational energy level transitions and significantly increasing the internal energy of the molecules.

[0039] The micro-vibration waves, generated synchronously by the piezoelectric effect, act on natural gas molecules, creating a perturbational physical field around the molecules. This perturbation effectively lowers the threshold for molecule absorption of radiant energy, further improving energy capture efficiency. Simultaneously, the micro-vibration waves cause slight deflections in the trajectories of natural gas molecules, increasing the probability of intermolecular collisions. Through continuous collisions, molecular clusters disaggregate into smaller active units.

[0040] The regulation and synergistic activation of the outer electron cloud of molecules, under the combined effects of electromagnetic radiation and micro-vibration waves, leads to reversible polarization and rearrangement of the outer electron cloud distribution in natural gas molecules. This electron cloud distortion weakens the dispersion forces that previously caused the molecules to become entangled and aggregated, resulting in molecular dissociation and orderly arrangement. Simultaneously, the change in the energy state of the outer electrons causes the surface charge distribution of the molecules to become more uneven, enhancing the electrostatic attraction and polarization matching between the molecules and oxygen molecules. This dual synergistic effect of electron cloud regulation and molecular deagglomeration is the core reason why the activation efficiency is significantly higher than that of single physical field treatment.

[0041] Changes in molecular motion properties and combustion-supporting reactions lead to the following changes in activated natural gas: First, the increased speed of motion and the increase in internal energy lead to a higher average speed of molecular motion and enhanced kinetic energy. Second, the motion trajectory is slightly perturbed. Affected by micro-vibration waves, the molecular motion path is in a state of slight perturbation, and the spatial distribution is more uniform. Third, the increased collision probability, combined with trajectory perturbation and molecular cluster deaggregation, increases the frequency of molecular collisions, further promoting the maintenance of the active state. Fourth, the molecular activity is enhanced; the polarization of the outer electron cloud puts the molecule in an excited state, significantly increasing its chemical activity. Fifth, it binds tightly to oxygen, increasing the polarization match between the activated molecule and the oxygen molecule, resulting in a tighter bond and a lower activation energy.

[0042] This invention provides a rare earth piezoelectric activated composite material for a multi-level resonant activation energy-saving device, comprising the following components in parts by weight: 65-85 parts piezoelectric ceramic powder, 8-25 parts rare earth functional material powder, 2-7 parts interface regulation agent, and 5-15 parts inorganic binder porous carrier powder. Among them, piezoelectric ceramic powder is the piezoelectric main phase, rare earth functional material powder is the rare earth infrared resonance activated phase, interface regulation agent is the interface regulation phase, and inorganic binder porous carrier powder is the porous carrier phase.

[0043] In this invention, the piezoelectric ceramic powder includes barium titanate, potassium sodium niobate, sodium bismuth titanate, and bismuth ferrite.

[0044] In this invention, the mass ratio of barium titanate, potassium sodium niobate, sodium bismuth titanate, and bismuth ferrite is preferably 46~56:9~12:7~10:3~7, and more preferably 49~52:10~11:8~9:4~6.

[0045] In this invention, the rare earth functional material powder includes neodymium oxide and lanthanum oxide, and the mass ratio of neodymium oxide to lanthanum oxide is preferably 6~15:2~10, more preferably 6~10:2~5.

[0046] In this invention, the interface regulation agent includes zirconium dioxide and manganese dioxide, and the mass ratio of zirconium dioxide to manganese dioxide is preferably 1~5:1~2, more preferably 4:1.

[0047] In this invention, the inorganic binder porous carrier powder includes kaolin, alumina and silica, preferably kaolin.

[0048] This invention also provides a method for preparing the above-mentioned rare earth piezoelectric activated composite material, comprising the following steps: S1. Ingredient mixing: Piezoelectric ceramic powder, rare earth functional material powder, interface control agent and inorganic binder porous carrier powder are ball-milled with a mixing grinding ball in anhydrous ethanol medium to obtain a mixture. The mixture is then dried at high temperature to obtain a mixed powder. S2, Pre-firing treatment: The mixed powder was calcined at high temperature in a muffle furnace to obtain pre-calcined powder; S3, Granulation and molding: A binder aqueous solution is added to the pre-fired powder, and after stirring, granulation, and aging, a ceramic green body is obtained by compression process. S4, Debinding and Sintering: The ceramic blank was sintered at high temperature in an air atmosphere in a muffle furnace, and after cooling, a rare earth piezoelectric composite activated ceramic material was obtained.

[0049] In this invention, the grinding balls in S1 are a combination of two diameter grinding balls, 5mm and 10mm.

[0050] The mass ratio of the mixed grinding balls is 1:1.

[0051] The mass ratio of material:ball:anhydrous ethanol is 1:2:1.

[0052] The ball milling speed is 300 rpm, and the time is preferably 8~16h, more preferably 12h.

[0053] The preferred high-temperature drying temperature is 80~120℃, more preferably 100℃, and the time is 12h.

[0054] In this invention, the high-temperature calcination temperature in S2 is preferably 600~700℃, more preferably 650℃, and the time is 2h.

[0055] In this invention, the binder aqueous solution in S3 is a polyvinyl alcohol binder aqueous solution with a concentration of 5% and an addition amount of 8% of the mass of the pre-calcined powder.

[0056] The aging time is 24 hours.

[0057] The compression process is a dry compression process, with a preferred pressure of 15~30MPa, more preferably 20MPa, and a holding time of 60s.

[0058] In this invention, the high-temperature debinding sintering parameters in S4 are as follows: the temperature is increased to 450~550℃, preferably 500℃, at a heating rate of 1.5℃ / min, and held for 2~3h, preferably 2h; then the temperature is increased to 1120~1220℃, preferably 1160℃, at a heating rate of 2℃ / min, and held for 2~4h, preferably 3h.

[0059] Example 1 This embodiment provides a rare earth piezoelectric activated composite material, which is composed of the following raw materials in parts by weight: 50 parts barium titanate, 10 parts potassium sodium niobate, 8 parts sodium bismuth titanate, 5 parts bismuth ferrite, 10 parts neodymium oxide, 5 parts lanthanum oxide, 4 parts zirconium dioxide, 1 part manganese dioxide, and 5 parts kaolin.

[0060] The preparation process of the above rare earth piezoelectric activated composite material is as follows: Piezoelectric ceramic powder, rare earth functional material powder, interface regulating agent, and inorganic binder porous carrier powder were mixed with 5 mm and 10 mm diameter grinding balls in anhydrous ethanol medium at a mass ratio of 1:1 and a material:ball:anhydrous ethanol mass ratio of 1:2:1. The mixture was ball-milled at 300 rpm for 12 hours to obtain a homogeneous mixture. The mixture was then dried in a 100℃ oven for 12 hours, pulverized, and sieved to obtain a mixed powder. The mixed powder was placed in a muffle furnace and heated to 650°C at a heating rate of 2°C / min. The temperature was held for 2 hours and then cooled to room temperature with the furnace to obtain the pre-calcined powder. Add a 5% polyvinyl alcohol binder aqueous solution to the pre-fired powder, the amount of which is 8% of the mass of the pre-fired powder. After stirring and granulation, age for 24 hours. Then, use a dry pressing process to press the ceramic blank into a circular sheet with a diameter of 20 mm and a thickness of 3 mm under a pressure of 20 MPa for 60 seconds. The ceramic blank was placed in a muffle furnace and heated to 500°C at a rate of 1.5°C / min under an air atmosphere. It was held at this temperature for 2 hours to remove the binder. Then, the temperature was increased to 1160°C at a rate of 2°C / min and held at this temperature for 3 hours for sintering. After sintering, the temperature was reduced to 800°C at a rate of 1°C / min and cooled to room temperature with the furnace to obtain the finished product 1.

[0061] Example 2 The preparation method of this embodiment is the same as that of Example 1, except that the ratio of piezoelectric ceramic powder and rare earth functional material powder is adjusted to 46 parts barium titanate, 9 parts potassium sodium niobate, 10 parts sodium bismuth titanate, 7 parts bismuth ferrite, 12 parts neodymium oxide, and 6 parts lanthanum oxide to obtain product 2.

[0062] Example 3 The preparation method of this embodiment is the same as that of Example 1, except that the proportion of rare earth functional material powder and the amount of inorganic binder porous carrier powder are adjusted to 8 parts of neodymium oxide, 4 parts of lanthanum oxide and 8 parts of kaolin to obtain product 3.

[0063] Example 4 The preparation method of this embodiment is the same as that of Example 1, except that the proportions of rare earth functional material powder, interface control agent and inorganic bonding porous carrier powder are adjusted to 6 parts of neodymium oxide, 4 parts of lanthanum oxide, 3 parts of zirconium dioxide, 1 part of manganese dioxide and 8 parts of kaolin, to obtain product 4.

[0064] Example 5 The preparation method of this embodiment is the same as that of Example 1, except that the inorganic bonding porous carrier powder is changed to alumina to obtain the finished product 5.

[0065] Comparative Example 1 The preparation method of this embodiment is the same as that of Example 1, except that the piezoelectric ceramic powder is adjusted to 75 parts of barium titanate.

[0066] Comparative Example 2 The preparation method of this embodiment is the same as that of Example 1, except that rare earth functional material powder is not added.

[0067] Comparative Example 3 The preparation method in this embodiment is the same as that in Example 1, except that no interface regulation agent is added.

[0068] Application example: The rare earth piezoelectric activated composite materials prepared in Examples 1-5 and Comparative Examples 1-3 were used to fabricate modular active components, which were then connected to the DN50-DN300 standard flange interface at the front end of the natural gas inlet. The system was tested at an operating temperature of 380℃ and a standard gas flow rate of 45 Nm³. 3 The concentrations of methane, CO, and HC in the outlet natural gas were tested at a certain temperature ( / h). Simultaneously, using Comparative Example 2 as a baseline, the activation energy of methane, the relative decrease in CO emissions, and the relative decrease in HC emissions were calculated based on the operating temperature and the measured total flow rate under standard pipeline conditions. The results are shown in Tables 1 and 2. Figures 1-4 .

[0069] Table 1. Test results of natural gas outlet gas components

[0070] From Table 1 and Figure 1 and Figure 2 It can be seen that the average outlet methane concentration in Examples 1-5 was 8.42-9.12 vol%, the average outlet CO concentration was 141-423 ppm, and the average outlet total hydrocarbon (HC) concentration was 1.6-5.5 mg·m³. -3 All were lower than the average methane concentration at the outlet of comparative examples 1-3, which was 9.30-9.74 vol%, with an average CO concentration of 451-564 ppm and total hydrocarbon (HC) of 5.6-6.4 mg·m³. -3 This indicates that the rare-earth piezoelectric activated composite material is selectively absorbed by combustion gas molecules through characteristic infrared radiation, effectively enhancing combustion reactivity and reducing emissions of methane, carbon monoxide, and total hydrocarbon pollutants in the exhaust gas. Comparative Example 1, adjusted to a single-phase piezoelectric master phase, showed a significant decrease in catalytic purification performance. Comparative Example 2 lacked a rare-earth infrared resonance activated phase, resulting in insufficient catalytic active sites and a substantial reduction in oxidation catalytic capacity. Comparative Example 3 lacked interface regulation aids, leading to a deterioration in the interfacial bonding between powders, a decrease in the interfacial transfer efficiency between the piezoelectric and catalytic phases, weakened interfacial synergy, and a decline in catalytic purification performance.

[0071] Table 2 Test Results of Methane Activation Energy and Relative Reduction in Pollutant Emissions

[0072] From Table 2 and Figure 3 and Figure 4It can be seen that the methane activation energy of Examples 1-5 is 80-100 kJ / mol, significantly lower than that of the comparative examples. CO emissions decreased by 25%-75% and HC emissions by 14%-75%, demonstrating significant pollutant reduction effects. Comparative Examples 1 and 3 had methane activation energies of 150 kJ / mol and 140 kJ / mol, respectively, with substantial reductions in CO and HC emissions. Comparative Example 2 had a methane activation energy as high as 240 kJ / mol, showing almost no pollutant reduction effect. This indicates that the complete formulation can effectively reduce the methane reaction activation energy, lower the reaction energy barrier, and improve the conversion and purification efficiency of methane, CO, and HC. Rare earth functional materials, interface control agents, and specific piezoelectric ceramic components are all indispensable for reducing the methane activation energy and exerting the synergistic purification effect of piezoelectricity and catalysis. The absence or replacement of key components will significantly increase the methane activation energy and significantly reduce the pollutant purification capacity.

[0073] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit them. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can still be made to the technical solutions of the present invention, and these modifications or equivalent substitutions cannot cause the modified technical solutions to deviate from the spirit and scope of the technical solutions of the present invention.

Claims

1. A composite material for a multi-stage resonant activation energy-saving device, characterized in that, The components include the following parts by mass: 65-85 parts of piezoelectric ceramic powder, 8-25 parts of rare earth functional material powder, 2-7 parts of interface regulation agent, and 5-15 parts of inorganic binder porous carrier powder. Among them, piezoelectric ceramic powder is the piezoelectric main phase, rare earth functional material powder is the rare earth infrared resonance activated phase, interface regulation agent is the interface regulation phase, and inorganic binder porous carrier powder is the porous carrier phase.

2. The composite material for the multi-stage resonant activation energy-saving device according to claim 1, characterized in that, The piezoelectric ceramic powder includes barium titanate, potassium sodium niobate, sodium bismuth titanate, and bismuth ferrite.

3. The composite material for the multi-stage resonant activation energy-saving device according to claim 2, characterized in that, The mass ratio of barium titanate, potassium sodium niobate, sodium bismuth titanate, and bismuth ferrite is 46~56:9~12:7~10:3~7.

4. The composite material for the multi-stage resonant activation energy-saving device according to claim 1, characterized in that, The rare earth functional material powder includes neodymium oxide and lanthanum oxide; The mass ratio of neodymium oxide to lanthanum oxide is 6~15:2~10.

5. The composite material for the multi-stage resonant activation energy-saving device according to claim 1, characterized in that, The interface regulation aids include zirconium dioxide and manganese dioxide.

6. The composite material for the multi-stage resonant activation energy-saving device according to claim 5, characterized in that, The mass ratio of zirconium dioxide to manganese dioxide is 1~5:1~2.

7. The composite material for the multi-stage resonant activation energy-saving device according to claim 1, characterized in that, The inorganic binder porous carrier powder includes kaolin, alumina and silica.

8. A method for preparing the composite material for the multi-level resonant activation energy-saving device according to any one of claims 1 to 7, characterized in that, Includes the following steps: S1. Ingredient mixing: Piezoelectric ceramic powder, rare earth functional material powder, interface control agent and inorganic binder porous carrier powder are ball-milled with a mixing grinding ball in anhydrous ethanol medium to obtain a mixture. The mixture is then dried at high temperature to obtain a mixed powder. S2, Pre-firing treatment: The mixed powder was calcined at high temperature in a muffle furnace to obtain pre-calcined powder; S3, Granulation and molding: A binder aqueous solution is added to the pre-fired powder, and after stirring, granulation, and aging, a ceramic green body is obtained by compression process. S4, Debinding and Sintering: The ceramic blank was sintered at high temperature in an air atmosphere in a muffle furnace, and after cooling, a rare earth piezoelectric composite activated ceramic material was obtained.

9. The method for preparing the composite material for the multi-stage resonant activation energy-saving device according to claim 8, characterized in that, The grinding balls described in S1 have diameters of 5 mm and 10 mm; The mass ratio of the mixed grinding balls is 1:1; The mass ratio of the material, spheres, and anhydrous ethanol is 1:2:

1. The ball milling speed is 300 rpm, and the time is 8~16 hours; The high-temperature drying temperature is 80~120℃, and the time is 12h; The high-temperature calcination temperature described in S2 is 600~700℃, and the time is 2h.

10. The method for preparing the composite material for the multi-level resonant activation energy-saving device according to claim 8, characterized in that, The binder aqueous solution mentioned in S3 is a polyvinyl alcohol binder aqueous solution with a concentration of 5% and an addition amount of 8% of the mass of the pre-calcined powder; The aging time is 24 hours; The compression process is a dry compression process, with a pressure of 15~30MPa and a holding time of 60s; The high-temperature debinding sintering parameters described in S4 are as follows: heating to 450~550℃ at a heating rate of 1.5℃ / min, holding for 2~3h, and then heating to 1120~1220℃ at a heating rate of 2℃ / min, holding for 2~4h.